LINKING DISSOLVED ORGANIC CARBON SPATIAL HETEROGENEITY TO GROUNDWATER DYNAMICS AND SOIL ORGANIC CARBON CONTENT IN A SUBTROPICAL HEADWATER CATCHMENT - Cesar Augusto Crovador Siefert; Irani dos Santos (Revista Brasileira de Geomorfologia, 2021)
Storage and fluxes of dissolved organic carbon (DOC) are triggered by interactions between hydrological and biogeochemical processes in the landscape. However, the relationship between DOC sources and catchment water storage is poorly understood due to uncertainties about the interactions between shallow groundwater (GW) dynamics and soil organic carbon (SOC). To investigate the relationships between catchment functioning and the spatiotemporal variability of DOC concentrations in shallow GW, we monitored a network of 12 shallow GW wells in a 0.24 km² catchment in Southern Brazil using DOC analysis and SOC measurements together with GW and stream gauging and statistical analyses. The greatest DOC concentration was observed in wells in the zero-order basin with highly dynamic saturation of the soil profile (50% with water table level below 0.5 m, mean DOC = 4.83 ± 2.53 mg L-1), where GW was characterized by a fast rise and slow decay during storm events. In these areas, the relationship between DOC concentration and GW level followed a decay with soil depth and higher DOC concentrations were found when GW level was within 0.1 m of the soil surface (ranging from 2.00 to 14.8 mg L-1). Wells in mid-slope locations were characterized by the lowest SOC content and DOC concentration in GW (1.96 ± 0.91 mg L-1). During the driest period, lower slopes showed higher DOC concentrations than riparian zones due to the persistent near saturation of GW and the occurrence of DOC-enriched water due to the high SOC content in superficial layers. When the riparian zone and hillslopes showed a low water storage deficit and a quasi-permanent hydrological connectivity, DOC produced between rainfall events was transported continuously from saturated areas in hillslopes to riparian zones, with a higher DOC concentration in wells near streams. This study demonstrates that spatial sources of DOC in a subtropical headwater system are linked to streamflow generation processes and GW dynamics.